Visual Recovery Following Primary Corneal Tear Repair in Penetrating Ocular Trauma: A Prospective Observational Study - Sana Shafqat, Fareeha Mirza, Tariq Pervaiz Khan, Fakhar Humayun, Muhammad Aamir Khan, Abdullah Humayun, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Penetrating ocular trauma frequently results in corneal tears requiring urgent globe repair topreserve anatomical integrity and visual function. This study investigates the visual outcomesfollowing corneal tear repair in patients presenting with penetrating eye trauma.